Autonomic Neuropathy and Albuminocytologic Dissociation in Cerebrospinal Fluid As the Presenting Features of Primary Amyloidosis: A Case Report - Li, Jingjing; Li, Yi; Chen, Hongbing; Xing, Shihui; Feng, Huiyu; Liu, Dawei; Wang, Dilong; Zeng, Jinsheng; Fan, Yuhua (Frontiers in Neurology, 2017)
Objective: Primary amyloidosis is a disease with a poor prognosis and multi-organ involvement. Here, we report the clinical and pathological features of a patient with primary amyloidosis featuring autonomic neuropathy as the initial symptom and albuminocytologic dissociation in the cerebralspinal fluid (CSF). Methods: The patient was a 60-year-old Chinese male patient with numbness, orthostatic hypotension and gastrointestinal symptoms. For diagnosis, we performed an electromyogram, lumbar puncture, Bence Jones protein urine test, serum electrophoresis blood test, sural nerve and rectal membrane biopsies, transthyretin (TTR) gene sequencing and bone marrow puncture. Results: Congo red staining of sural nerve and rectal membrane biopsies showed amyloid deposition and apple-green birefringence was visualized under polarized light microscopy. TTR gene sequencing showed no causative mutation. Following lumbar puncture, normal CSF cell counts and elevated CSF protein concentration (1680 mg/L) were detected. Bone marrow puncture showed that out of the total number of whole blood cells, 0.56% were abnormal plasma cells, and that 87.4% of the total number of plasma cells were abnormal. Electromyogram results showed mixed peripheral nerve damage predominately in the sensory nerve fibers. Conclusions:Obvious symptoms of neuropathy, particularly autonomic neuropathy, albuminocytologic dissociationand organ function damage suggested a diagnosis of amyloidosis. In such patients, neurologists should use caution to differentiate between chronic inflammatory demyelinating polyneuropathy, primary amyloidosis and familial amyloid neuropathy.